ANEURYSM OF THE SUBCLAVIAN ARTERY - Utikal, Petr; Bachleda, Petr; Kocher, Martin; Novotny, Josef; Drac, Petr; Drac, Pavel (Biomedical papers, 1999)
In this case report about a female patient with a true aneurysm of the left subclavian artery (SAA), the authorswould like to present the symptoms, possibilities of diagnostics and management of this rarely appearing pathology.The diagnosis of a randomly found aneurysm in a symptomfree patient was confirmed by spiral AGCT. Classicalsurgical procedure was indicated for the patient. With a combined supra- infraclavicular approach the partialresection of the aneurysm and its revascularization by a ePTFE prosthetic interposition were performed. Ahistological investigation showed nonspecific changes in the aneurysm wall. Two years after the operation thepatient is without any complications and with complete functional vascular reconstruction and optimal limbfunction.
Keywords: Subclavian artery / True aneurysm / ePTFE Prosthesis